A two-phase simulation–optimization cellular automata method for sewer network design optimization. Issue 4 (2nd April 2020) - Zaheri, M. M.; Ghanbari, R.; Afshar, M. H.
ABSTRACT: In this paper, a Cellular Automata based simulation-optimization approach is proposed for the optimal design of household sewer networks. A two-phase CA is used as the optimization tool while the EPA's storm water management model (SWMM) is used as the simulator. A splitting method is first used to redefine the sewer network design problem in terms of two simpler sub-problems with diameters and nodal elevations of each pipe as decision variables which are iteratively solved using CA methods in two-stage manner until convergence is achieved. Each CA uses a separate ad-hoc local rule to update the cell state of the corresponding problem derived using engineering judgment and the hydraulic principles of the sewer flow. The proposed method is applied to some benchmark sewer networks and the results are presented and compared to those of the existing methods. Results indicates the efficiency and effectiveness of the proposed methods compared to the existing methods.